2015
DOI: 10.1039/c5ra13771c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a novel fluorinated bismaleimide via a nucleophilic addition–elimination reaction and its polymeric networks

Abstract: A novel fluorinated bismaleimide, OFCP-BMI, was designed and readily synthesized via the nucleophilic addition–elimination reaction of octafluorocyclopentene with maleimide-functionalized phenol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…However, relative to reagents 1 and 2 , we sought broader nucleophile participation and product geometries that are more compatible with smaller polyheterocyclic structures. Rather than aromatic substitutions, we choose to examine vinylic substitutions of fluoride from octafluorocyclopentene (OFCP, 3 ; Figure ) . Simple phenols, amines, mercaptans, and alcohols are known to displace fluoride from this commercial reagent, and the extent of substitution could be varied.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…However, relative to reagents 1 and 2 , we sought broader nucleophile participation and product geometries that are more compatible with smaller polyheterocyclic structures. Rather than aromatic substitutions, we choose to examine vinylic substitutions of fluoride from octafluorocyclopentene (OFCP, 3 ; Figure ) . Simple phenols, amines, mercaptans, and alcohols are known to displace fluoride from this commercial reagent, and the extent of substitution could be varied.…”
Section: Figurementioning
confidence: 99%
“…[6] Thee ase of fluoride ipso substitutions was appealing.H owever,r elative to reagents 1 and 2,wesought broader nucleophile participation and product geometries that are more compatible with smaller polyheterocyclic structures.R ather than aromatic substitutions,w ec hoose to examine vinylic substitutions of fluoride from octafluorocyclopentene (OFCP, 3; Figure 1). [7][8][9][10][11][12][13][14][15][16] Simple phenols, [7] amines, [10] mercaptans, [14,15] and alcohols [14][15][16] are known to displace fluoride from this commercial reagent, and the extent of substitution could be varied. Herein, we report that successive,d issymmetric substitutions [17] of fluoride on OFCP by functionalized peptides occurs readily,w hich provides af lexible means to generate constrained fluorinated macrocycles.…”
mentioning
confidence: 99%
“…Recently, we accidently discovered the fluoride ion can initiate the polymerization of N ‐substituted maleimide to yield a polymeric byproduct during preparing a novel fluorinated bismaleimide . After a literature research, we found only one previous study showed the fluoride ion can induce the polymerization of N ‐methylmaleimide, which was used for fluoride ion detection and only dimer, trimer, and oligomer were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Another effective strategy is the modification of BMI's chemical structure. A number of new chain‐extended BMIs have been designed and synthesized, such as those containing amide, ester, naphthalene, phosphorus, silicon, 1,3,4‐oxadiazole, biphenylene, dicyclopentadiene or dipentene, fluorenyl, parabanic, allyl, s‐triazine, phenylindane, azobenzene, epoxy backbone, and metal complex . Based on the structure–properties relationships, the unsymmetrical chemical structure can hinder the ordered packing or crystallization of the molecules, hence improve the solubility of the monomers.…”
Section: Introductionmentioning
confidence: 99%